If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15x-6x=(-x+3)-(x+2+10)
We move all terms to the left:
15x-6x-((-x+3)-(x+2+10))=0
We add all the numbers together, and all the variables
15x-6x-((-1x+3)-(x+12))=0
We add all the numbers together, and all the variables
9x-((-1x+3)-(x+12))=0
We calculate terms in parentheses: -((-1x+3)-(x+12)), so:We get rid of parentheses
(-1x+3)-(x+12)
We get rid of parentheses
-1x-x+3-12
We add all the numbers together, and all the variables
-2x-9
Back to the equation:
-(-2x-9)
9x+2x+9=0
We add all the numbers together, and all the variables
11x+9=0
We move all terms containing x to the left, all other terms to the right
11x=-9
x=-9/11
x=-9/11
| 4x+6=8x+9 | | 2x+41=5x-4 | | 280*2.67+770*x-6.13*742=0 | | 130x=180 | | 0=10x-(40000+6x) | | -3+11=14x-5-13x | | 6(x-7)-8x=-32 | | -17-(-28)=x/7 | | 2x+20+110=180 | | 19x=7x=180 | | w+7=5w-7 | | 2x-12÷3=8 | | X^2+7/2x=23/4 | | 5=13+x/3 | | 2x-15=-3x=5 | | 2x-15=4x+11 | | 5=6,5*2+x/3 | | 40x+(8*1.5x)=750 | | 6x-(4x+5)=21 | | (7p+1)(7p−2)=0 | | 81=9-8v | | (-2)=2-5x | | 3z=7z-1 | | 3x+1-2x=11 | | 1/2x-2=1/4x+6 | | 12-3(5x+2)=4(-3x+7)-1 | | -2(3x+6)=4(x+7) | | t/5+8=2 | | -3x+7=4x-49 | | 14-2(4-p)=54 | | 3(2-4w)=54 | | 10-{r}{3}=-2 |